Effect of food source availability in the salivary gland transcriptome of the unique burying beetle Nicrophorus pustulatus (Coleoptera: Silphidae). - Christian O Ayala-Ortiz; Jacob W Farriester; Carrie J Pratt; Anna K Goldkamp; Jessica Matts; W Wyatt Hoback; John E Gustafson; Darren E Hagen (PLoS ONE, 2021)
Nicrophorus is a genus of beetles that bury and transform small vertebrate carcasses into a brood ball coated with their oral and anal secretions to prevent decay and that will serve as a food source for their young. Nicrophorus pustulatus is an unusual species with the ability to overtake brood of other burying beetles and whose secretions, unlike other Nicrophorus species, has been reported not to exhibit antimicrobial properties. This work aims to better understand how the presence or absence of a food source influences the expression of genes involved in the feeding process of N. pustulatus. To achieve that, total RNA was extracted from pooled samples of salivary gland tissue from N. pustulatus and sequenced using an Illumina platform. The resulting reads were used to assemble a de novo transcriptome using Trinity. Duplicates with more than 95% similarity were removed to obtain a "unigene" set. Annotation of the unigene set was done using the Trinotate pipeline. Transcript abundance was determined using Kallisto and differential gene expression analysis was performed using edgeR. A total of 651 genes were found to be differentially expressed, including 390 upregulated and 261 downregulated genes in fed insects compared to starved. Several genes upregulated in fed beetles are associated with the insect immune response and detoxification processes with only one transcript encoding for the antimicrobial peptide (AMP) defensin. These results confirm that N. pustulatus does not upregulate the production of genes encoding AMPs during feeding. This study provides a snapshot of the changes in gene expression in the salivary glands of N. pustulatus following feeding while providing a well described transcriptome for the further analysis of this unique burying beetle.